Institutional Arrangements: Policies and Administrative Mechanisms on Water Governance in the Kingdom of Cambodia - Seng, Soun; Keartha, Chay; Phyrom, Seang; Pech, Sokhem (CGIAR Challenge Program on Water and Food, 2013)
The findings and discussions show that in the recent decades Cambodia has developed extensive policies related to water-based and water related sectors. Such policies are aimed at ensuring equitable and sustainable development of the nation. Many external players (bilateral partners and multilaterals partners) have facilitated the RGC in developing these policies and legal instruments. However, due to insufficient financial resources, the government institutions in Cambodia are still largely dependent on donor support for implementing development projects. Thus, some policies and legal instruments are not yet fully implemented owing to lack of financial resources.